Australian mycophagous species of the genus Deplorothrips (Thysanoptera, Phlaeothripinae) - Mound, Laurence A.; Tree, Desley J. (Zootaxa, 2016)
The genus Deplorothrips Mound & Walker is recorded from Australia for the first time. The genus is found widely across the continent, and descriptions and an illustrated identification key are provided to 14 new species. These have been found living on dead twigs and branches, particularly of Eucalyptus trees. Typical members of this genus have short maxillary stylets that are scarcely retracted into the head capsule, but some of the species have more deeply retracted stylets. Structural polymorphism is recorded in several species, associated both with sex and with body size. Remarkable variation is recorded for some species in the number of sense cones on the antennal segments.